Modulation of physiological performance by temperature and salinity in the sugar kelp Saccharina latissima. Issue 1 (27th October 2020) - Monteiro, Cátia; Li, Huiru; Diehl, Nora; Collén, Jonas; Heinrich, Sandra; Bischof, Kai; Bartsch, Inka
SUMMARY: The sugar kelp Saccharina latissima experiences a wide range of environmental conditions along its geographical and vertical distribution range. Temperature and salinity are two critical drivers influencing growth, photosynthesis and biochemical composition. Moreover, interactive effects might modify the results described for single effects. In shallow water coastal systems, exposure to rising temperatures and low salinity are expected as consequence of global warming, increased precipitation and coastal run‐off. To understand the acclimation mechanisms of S. latissima to changes in temperature and salinity and their interactions, we performed a mechanistic laboratory experiment in which juvenile sporophytes from Brittany, France were exposed to a combination of three temperatures (0, 8 and 15°C) and two salinity levels (20 and 30 psu (practical salinity units)). After a temperature acclimation of 7 days, sporophytes were exposed to low salinity (20 psu) for a period of 11 days. Growth, and maximal quantum yield of photosystem II ( F v/ F m), pigments, mannitol content and C:N ratio were measured over time. We report for the first time in S. latissima a fivefold increase in the osmolyte mannitol in response to low temperature (0°C) compared to 8 and 15°C that may have ecological and economic implications. Low temperatures significantly affected all parameters, mostly in a negative way. Chlorophyll a, the accessory pigment pool, growth and F v/ F m were significantly lower at 0°C, while the de‐epoxidation state of the xanthophyll cycle was increased at both 0 and 8°C compared to 15°C. Mannitol content and growth decreased with decreased salinity; in contrast, pigment content and F v/ F m were to a large extent irresponsive to salinity. In comparison to S. latissima originating from an Arctic population, despite some reported differences, this study reveals a remarkably similar impact of temperature and salinity variation, reflecting the large degree of adaptability in this species.